Eccrine sweat glands associate with the human hair follicle within a defined compartment of dermal white adipose tissue. (1st May 2018) - Poblet, E.; Jimenez, F.; Escario‐Travesedo, E.; Hardman, J.A.; Hernández‐Hernández, I.; Agudo‐Mena, J.L.; Cabrera‐Galvan, J.J.; Nicu, C.; Paus, R.
Summary: It has always been assumed that sweat glands are distributed throughout the skin unconnected with hair follicles (hair "roots") and their associated sebaceous (or "grease") glands, which, together with other specialised glands and the muscles that make hairs stand up, are known as pilosebaceous units. Sweat glands and pilosebaceous units, in other words, have always been considered separate structures, with sweat glands opening on to the skin surface between hairs rather than alongside them. Sweat glands on the palms of the hands and the soles of the feet develop differently and were not considered in this study. Using a number of techniques, including looking down the microscope at sections of hair follicles taken from the scalp during hair transplants, and at manual and computer‐assisted 3D reconstructions of sections of scalp skin, this study from Spain and Manchester, UK, suggests that in hair‐bearing areas the deepest part of the sweat gland, a coiled structure, is in fact located very close to the deepest part of the pilosebaceous unit, sitting right by the sheath of the hair follicle, below the sebaceous gland and the point where the hair muscle attaches. Moreover, these structures sit together within cone‐shaped projections of fat that reach upwards into the lowest layer of the skin, the thick reticular dermis, from the fat underneath. The authors speculate that sweat glands, pilosebaceous units and this particular fatty tissue (collectively the "adnexal skin unit") may interact in certain skin diseases, during wound healing and with drug treatments.